Metabolomics Reveals the Mechanism by Which Sodium Butyrate Promotes the Liver Pentose Phosphate Pathway and Fatty Acid Synthesis in Lactating Goats - Lin Li; Xi Chen; Shuping Yan; Yuanshu Zhang (Animals)
This study aimed to explore the effects of sodium butyrate on liver metabolism in goats subjected to a high-concentrate diet. We randomly assigned twelve Saanen-lactating goats into two groups, one of which received a high-concentrate diet (concentrate: forage = 60:40, control group), while the other received the same basal diet supplemented with sodium butyrate (SB) (10 g/kg basal diet, SB group). Compared with the control diet, the SB diet considerably increased the milk fat percentage and content (p < 0.05), with an increase of 0.67% in the milk fat content of the SB group. By employing a global metabolomics approach based on ultra-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS), we identified 6748 ions in ESI+ mode and 3573 ions in ESI− mode after liver isolation from both groups. A total of twenty-three metabolites, including phospholipids, fatty acids, and ribose phosphate, were found to be dysregulated according to a search against the human metabolome database (HMDB). Pathway analysis revealed activation of the pentose phosphate pathway, glycerophospholipid metabolism, and unsaturated fatty acid synthesis. The SB diet also modulated the expression of key lipogenic enzymes, such as acetyl-CoA carboxylase (ACC) and stearoyl-CoA desaturase (SCD-1), which are downstream targets of the transcription factor sterol regulatory element-binding proteins-1c (SREBP-1c), inducing a significant upregulation (p < 0.05). Furthermore, 6-phosphogluconate dehydrogenase (6PGDH) levels in the liver were elevated after the lactating goats were fed the SB diet (p < 0.05). Our study reveals that the SB diet may offer substantial benefits in enhancing the milk quality of subacute ruminal acidosis (SARA) goats. This is accomplished by augmenting the activity of the liver pentose phosphate pathway and the process of de novo fatty acid synthesis in lactating goats.